Ecology and management of Quercus coccifera L. shurblands in Spain - Cañellas, I. (Forest Systems, 1991)
Evergreen sclerophyllous shrublands constitute an important part of Mediterranean rangelands, being the dominant species Kermes oak (Quercus coccifera L.). The conservation of these shrublands is justified by their protection of soils against erosion and by their foodder production for domestic and wild animals. The impact of fire in Quercus coccifera garrigues in the South-West of Spain was analysed through a synchronic study (indirect approach) evaluating the process of organization and structure of this community.